Jaringan Syaraf Tiruan Menggunakan Metode Backpropagation Dalam Prediksi Persediaan Bahan Baku (Studi Kasus : PT. Bintang Toba Lestari) - Atmaja, Niko Surya; Lianda, Deri (Informasi Interaktif, 2021)
Â PT. Bintang Toba Lestari is a spring bed manufacturer located in the city of Medan. In providing spring bed raw materials for spring bed production, PT. Bintang Toba Lestari usually estimates based on inventory notebooks so that the results of predictions made often miss estimates because there are no proper calculations to make predictions. This can be detrimental to the company because of the embedded capital. Embedded capital should be used for the company's regular expenses. Therefore, a system is needed that can help PT. Bintang Toba Lestari to be able to predict spring bed raw materials so that there is no embedded capital that causes the company's losses. This study uses neural networks to predict the supply of spring bed raw materials and uses backpropagation methods to process spring bed raw material inventory data so as to get the right forecasting results. With the existence of artificial neural networks using the backpropagation method, it can help PT. Bintang Toba Lestari in predicting spring bed raw material supplies .Keywords: Neural Networks, Backpropagation, Predictions, Supplies, Raw Materials.